2010
DOI: 10.1073/pnas.1002828107
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis resistance protein SNC1 activates immune responses through association with a transcriptional corepressor

Abstract: In both plants and animals, nucleotide-binding (NB) domain and leucine-rich repeat (LRR)-containing proteins (NLR) function as sensors of pathogen-derived molecules and trigger immune responses. Although NLR resistance (R) proteins were first reported as plant immune receptors more than 15 years ago, how these proteins activate downstream defense responses is still unclear. Here we report that the Toll-like/interleukin-1 receptor (TIR)-NB-LRR R protein, suppressor of npr1-1, constitutive 1 (SNC1) functions thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
259
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(279 citation statements)
references
References 32 publications
17
259
0
3
Order By: Relevance
“…The exact mechanism by which TPL restrains gene expression remains unclear. Some data point to a link with the histone deacetylase HDA19 (At4g38130; Long et al, 2006;Zhu et al, 2010), and a direct interaction has been reported between TPL and Jumonji8, a histone demethylase (Macrae and Long, 2011). Furthermore, a direct link between JAZ1 and HDA6 (At5g63110) has recently been established, although the JAZ domain necessary for this interaction has not been mapped precisely (Zhu et al, 2011).…”
Section: Jaz Functionmentioning
confidence: 99%
“…The exact mechanism by which TPL restrains gene expression remains unclear. Some data point to a link with the histone deacetylase HDA19 (At4g38130; Long et al, 2006;Zhu et al, 2010), and a direct interaction has been reported between TPL and Jumonji8, a histone demethylase (Macrae and Long, 2011). Furthermore, a direct link between JAZ1 and HDA6 (At5g63110) has recently been established, although the JAZ domain necessary for this interaction has not been mapped precisely (Zhu et al, 2011).…”
Section: Jaz Functionmentioning
confidence: 99%
“…In plants, activation of R proteins leads to extensive transcriptional reprogramming of defence genes (Chang etĀ al ., 2013; Inoue etĀ al ., 2013; Padmanabhan etĀ al ., 2013; Shen etĀ al ., 2007; Zhu etĀ al ., 2010). Different regulatory proteins may activate different kinds of genes in wheat defence response to R.Ā cerealis .…”
Section: Discussionmentioning
confidence: 99%
“…A more direct link between an R protein and SUMOylation is exemplified by the Arabidopsis thaliana SNC1 protein. SNC1 was shown to interact directly with TPR1 and HDA19, 10 which indicates that SNC1 and possibly related R proteins (i.e., TIR-NB-LRR proteins) interact in the nucleus with SUMO-modified transcriptional co-repressors. These repressors might prevent activation of the plant defense response in non-infected plants.…”
Section: Wrky Transcription Factors As Targets Of Sumoylationmentioning
confidence: 99%